ACCEPTING THE TRANSSEXUAL IN KIMBERLY PEIRCE'S BOYSDON'T CRY MOVIE (1999): A SOCIOLOGICAL APPROACH - ILMI, DAYU AMALIA (2011)
The major problem in this study is to show accepting the transsexual in Kimberly Peirce's Boys Don't Cry movie by using sociological approach. it is conducted by analyzing the movie based on its structural elements and analyzing some aspects in American society in the late twentieth century based on sociological theories. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is Boys Don't Cry movie directed by Kimberly Peirce released in 1999. While the secondary data sources are other materials taken from books, internet and other relevant information. Both data are collected through library research and analyzed by descriptive analysis. Using a sociological analysis as the theoretical framework, the research shows the following findings. First, based on structural analysis of this movie, it is evidence that there is accepting the transsexual in United States. Peirce has proven by delivering a message through its theme that the transsexual needs to be accepted in this movie. Second, based on sociological analysis, Peirce reflects the social phenomena in which people oppose those who have different sexual orientation from majority that is homosexuality. She seems to take side on major character, a transsexual since she respects every citizen who has right to live their life.